Allele frequency analysis of variants reported to cause autosomal dominant inherited retinal diseases question the involvement of 19% of genes and 10% of reported pathogenic variants. Issue 8 (25th March 2019) - Hanany, Mor; Sharon, Dror
Abstract : Background: Next generation sequencing (NGS) generates a large amount of genetic data that can be used to better characterise disease-causing variants. Our aim was to examine allele frequencies of sequence variants reported to cause autosomal dominant inherited retinal diseases (AD-IRDs). Methods: Genetic information was collected from various databases, including PubMed, the Human Genome Mutation Database, RETNET and gnomAD. Results: We generated a database of 1223 variants reported in 58 genes, including their allele frequency in gnomAD that contains NGS data of over 138 000 individuals. While the majority of variants are not represented in gnomAD, 138 had an allele count of >1 and were examined carefully for various aspects including cosegregation and functional analyses. The analysis revealed 122 variants that were reported pathogenic but unlikely to cause AD-IRDs. Interestingly, in some cases, these unlikely pathogenic variants were the only ones reported to cause disease in AD inheritance pattern for a particular gene, therefore raising doubt regarding the involvement of 11 (19%) of the genes in AD-IRDs. Conclusion: We predict that these data are not limited to a specific disease or inheritance pattern since non-pathogenic variants were mistakenly reported as pathogenic in various diseases. Our results should serve as a warning sign for geneticists, variant database curators and sequencing panels' developers not to automatically accept reported variants as pathogenic but cross-reference the information with large databases.